2017
DOI: 10.1177/1535370217703360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gonadectomy and testosterone treatment on aquaporin expression in the kidney of normotensive and hypertensive rats

Abstract: We tested the hypothesis that testosterone-induced increase in blood pressure was due to changes in aquaporin (AQP) expression in kidneys. In this study, expression level of kidney AQPs was investigated under testosterone influence. Adult normotensive Wistar Kyoto (WKY) and hypertensive SHR male and female rats underwent gonadectomy. For female rats, testosterone was given for six weeks duration, two weeks following ovariectomy via subcutaneous silastic implant. Mean arterial pressure (MAP) was measured in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Recently, Vasavan et al (2020) observed the same alterations in urea and creatinine with ND treatment. In this respect, Loh et al (2017) demonstrated that the elevated testosterone associated with AASs use increased the expression of aquaporins (AQPs) two four, and six in the collecting duct and AQPs-1 and sevene in the proximal convoluted tubule, consequently raised blood pressure, and increased water reabsorption resulting in hypertension and chronic kidney disease. Besides, AASs-induced direct glomerular toxicity due to increased body mass and glomerular hyperfiltration has been suggested as injury mechanisms (Parente Filho et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Vasavan et al (2020) observed the same alterations in urea and creatinine with ND treatment. In this respect, Loh et al (2017) demonstrated that the elevated testosterone associated with AASs use increased the expression of aquaporins (AQPs) two four, and six in the collecting duct and AQPs-1 and sevene in the proximal convoluted tubule, consequently raised blood pressure, and increased water reabsorption resulting in hypertension and chronic kidney disease. Besides, AASs-induced direct glomerular toxicity due to increased body mass and glomerular hyperfiltration has been suggested as injury mechanisms (Parente Filho et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A direct relationship between AAS use and kidney injury has been described in several animal studies. High levels of several cytokines (such as TNF-α) ( Patil et al., 2016 ) and hypertension can cause the development of glomerulosclerosis ( Doublier et al., 2011 ), generating injuries similar to CKD ( Loh et al., 2017 ). CKD is caused by the progressive development of glomerular fibrosis or glomerulosclerosis, interstitial fibrosis, consequent atrophy, loss of tubular epithelium, and chronic inflammation, also with the loss of the peritubular capillaries that causes a decrease in the glomerular filtration rate ( Nogueira et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone is involved in ammonia metabolism and excretion [126], water handling through increasing the expression of certain aquaporin subunits [127], and urinary calcium clearance [128]. Quant et al found that androgens may be involved in the upregulation of the renin-angiotensin system in the proximal tubules [18].…”
Section: Influence Of Sex Hormones In the Kidneymentioning
confidence: 99%